2012
DOI: 10.4103/0253-7613.96326
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of alternate-day versus everyday dosing of atorvastatin

Abstract: Background:Atorvastatin has a longer duration of action than other hydroxymethylglutaryl coenzyme A reductase inhibitors.Objectives:The objective was to evaluate the efficacy of alternate day vs. daily dosing of atorvastatin for the treatment of hyperlipidemia.Materials and Methods:In this prospective, open label, crossover study, 40 patients with plasma low-density cholesterol (LDL-C) of more than 130 mg/dl and total cholesterol (TC) more than 200 mg/dl were recruited. After baseline tests, they were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…In both the groups, a significant reduction in LDL-C was seen but the difference between the two groups was not statistically significant, findings similar to those of Matalka et al, Pramanik et al and Keles et al 6,14,15 Regarding the percentage of the participants achieving LDL-C levels <100 mg/dL, both the groups were comparable. A similar finding was seen in Matalka et al study where 43% patients from alternate day atorvastatin group and 75 % patients from daily atorvastatin group achieved LDL-C levels <100 mg/dL (p>0.05).…”
Section: -16supporting
confidence: 82%
See 1 more Smart Citation
“…In both the groups, a significant reduction in LDL-C was seen but the difference between the two groups was not statistically significant, findings similar to those of Matalka et al, Pramanik et al and Keles et al 6,14,15 Regarding the percentage of the participants achieving LDL-C levels <100 mg/dL, both the groups were comparable. A similar finding was seen in Matalka et al study where 43% patients from alternate day atorvastatin group and 75 % patients from daily atorvastatin group achieved LDL-C levels <100 mg/dL (p>0.05).…”
Section: -16supporting
confidence: 82%
“…Similar findings had been reported by Pramanik et al where there was 27.14% reduction in TC with alternate day atorvastatin therapy and 29% with daily atorvastatin therapy. 14 Juszczyk et al showed a greater percentage reduction in TC which might be because a higher dose (40 mg) of atorvastatin, used in their study. 8 The safety and tolerability elicited by both regimens in present study were consistent with the studies conducted by Keles et al, Jafari et al and Ghia et al 15,17,18 The adverse events were mild and none of the patients from either group discontinued the study drugs because of it.…”
Section: -16mentioning
confidence: 78%
“…These findings are cohesive with Pramanik S et al, Jafari M et al, Matalka MS, et al and Aghosadeghi K and Zare et al [6][7][8][9] A prospective, open label, crossover study in 40 patients conducted by Pramanik S et al evaluating the efficacy of alternate day atorvastatin versus daily dosing showed that both treatment regimens significantly reduced TC and TG and LDL-C levels as compared to baseline. There was no statistically significant difference between the two groups in terms of reduction of TC, TG and LDL-C at 12 weeks of treatment.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, the mean percentage increase of LDL-cholesterol from baseline to assessment at 6 weeks was significantly higher in those who were on atorvastatin every-other-day as compared to daily atorvastatin group (32.8% vs 1.5%). However, some other studies have shown that every-other-day dosing of atorvastatin is as effective as daily atorvastatin in controlling LDL-cholesterol [ [31] , [32] , [33] ]. Jafari et al conducted a randomized controlled trial in 54 patients and found that there was no difference in LDL-cholesterol level at 6 weeks between those who received atorvastatin 10 mg daily and 10 mg every-other-day [ 31 ].…”
Section: Discussionmentioning
confidence: 99%